A Critique of Muḥammad Shahrūr’s Views on the Qur’ān, the Ḥadīth Corpus, Sharīᶜah, and Early Islamic Scholarship - Ushama, Thameem (Advances in Social Sciences Research Journal, 2021)
This article describes the life, education, and thoughts of Muhammad Shahrūr, whose discourse on Islam generated confusion and much in the way of polemical debate. His controversial bias favoured modernity, influenced by modern Western epistemology, traditions, and secularism. The author applies qualitative content analysis to select writings. The analysis unveils his position (s) in light of mainstream Islam and focusses on Shahrūr’s approach to Islamic religious thought via (1) theories of Non-Synonymity and Limit; (2) his view of the Ḥadīth and Sharīᶜah; (3) the status of Muslim women with regard to polygamy, dress code and feminism; (4) the law of inheritance; (5) western culture and civilization; and (6) evolution; democracy, nationalism and pluralism, etc.